Case report: De novo mutation of a-galactosidase A in a female patient with end-stage renal disease: report of a case of late diagnosis of Anderson–Fabry disease - Simonetta, Irene; Riolo, Renata; Todaro, Federica; Donadio, Vincenzo; Incensi, Alex; Miceli, Salvatore; Colomba, Paolo; Duro, Giovanni; Tuttolomondo, Antonino (Frontiers in Genetics, 2023)
Background: Anderson-Fabry disease (AFD) is an X-linked disease that results from reduced activity of the enzyme galactosidase alpha (GLA). When the GLA gene sequence is altered by mutations that alter the normal DNA sequence, variants of the alpha-galactosidase A enzyme are produced, which may or may not function. These mutations are responsible for Fabry disease, and to date, over 800 different mutations of the gene have been described in patients with Anderson-Fabry disease. In this case, we report the case of a woman who is the only one in her family with this type of mutation.We report a case of a 52-year-old woman with end-stage chronic kidney disease in dialysis treatment. The patient's alpha-galactosidase activity was 6,6 nmol/ml/h in whole blood, and Lyso-GB3 levels were 11,45 nmol/l (normal range < 2,3 nmol/L). Alpha-galactosidase A gene sequence analysis revealed a pathogenetic variant of c.947dupT in exon six, leading to the p. I317NfsTer16 amino acid substitution. The genetic analysis did not detect the same mutation in any other screened family members.The International Fabry Disease Genotype-Phenotype Database (dbFGP) reports a pathogenetic variant c.947dupT in exon 6 that is probably associated with a classical phenotype of Fabry disease. In this case report, we report the case of a woman who is the only one in her family with this type of pathogenetic variant. Similar situations have not been described in the literature for this pathogenetic variant, and it represents an important case of inter-and intrafamilial variability in patients with Fabry disease. The literature shows that de novo pathogenetic variants are frequently found in the context of Fabry disease.